Nanang Sobarna Analisis Penerapan Maqashid Syariah Dalam Penyaluran Pembiayaan Pada Koperasi Syariah - Nanang Sobarna; Dady Nurpadi; Gina Nurafifah; Jeni Nurjaman (J-Coop : Journal of Co-operative, 2026)
This research aims to analyze the application of maqashid sharia in the distribution of financing in sharia cooperatives in Indonesia. Maqashid syariah, which is the main objective of sharia, focuses on the protection and enhancement of community welfare through principles of justice and balance in transactions. This research uses a qualitative approach with a literature study method. The research results show that Islamic cooperatives have implemented the principles of maqashid sharia in various aspects of financing distribution, such as in the selection of appropriate financing products, risk management, and transparency. Additionally, this research also identifies supporting and inhibiting factors in the implementation of maqashid sharia, as well as its impact on the welfare of cooperative members. These findings provide recommendations to enhance members' understanding of sharia finance and the need for better regulatory support for sharia cooperatives, in order to optimally achieve the goals of maqashid sharia.